A New Approach to the Mechanism of Fischer–Tropsch Syntheses Arising from Gas Phase NMR and Mass Spectrometry. Issue 9 (26th April 2016) - Bordet, Alexis; Lacroix, Lise‐Marie; Soulantica, Katerina; Chaudret, Bruno
Abstract: We used 13 CO labeling to show that gas‐phase NMR spectroscopy and mass spectrometry are simple tools for mechanistic investigations of the Fischer–Tropsch (FT) reaction. Thus, monodisperse Fe nanoparticles (NPs) react with syngas to form monodisperse iron carbide (FeC x ) NPs. As expected, the heating of 13 C‐labeled monodisperse FeC x NPs under H2 results in the desorption of the carbide carbons as 13 CH4 and, interestingly, restores the initial Fe NPs in terms of size and dispersity. The Fe 13 C x NPs catalyze the hydrogenation of 12 CO at 210 °C to yield only 12 C‐labeled FT products, which evidences the absence of the incorporation of FeC x carbon atoms in the products. In addition, this approach shows for the first time that the formation of 13 CH4 at 250 °C does not result from direct carbide hydrogenation but from an intermediate step that involves a reaction between Fe 13 C x and H2 O to give 13 CO2, which is subsequently hydrogenated. These results rule out the involvement of FeC x carbon atoms in the chain growth process under our conditions. Abstract : Not just a label : We report the synthesis of monodisperse iron carbide nanoparticles (NPs) through the addition of CO and H2 to monodisperse zero‐valent iron NPs. The reversibility of this reaction is evidenced. We use gas‐phase NMR spectroscopy and mass spectrometry to show that 13 CO labeling allows a mechanistic investigation of the Fischer–Tropsch reaction.